2014
DOI: 10.1002/acr.22423
|View full text |Cite
|
Sign up to set email alerts
|

High Risk of Pulmonary Embolism and Deep Venous Thrombosis but Not of Stroke in Granulomatosis With Polyangiitis (Wegener's)

Abstract: The present study confirms that GPA patients have a markedly increased risk of venous thromboembolism. We did not observe an increased risk of stroke in our cohort. Thus, our observations demonstrate a differential impact of GPA and/or its treatment on the risk of various vascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 23 publications
(37 reference statements)
1
23
1
3
Order By: Relevance
“…Overall, our study did not show a statistically significant increased risk of stroke in GPA patients compared with their matched controls. This finding is similar to that in a recent study by Faurschou et al in Denmark (51).…”
Section: Discussionsupporting
confidence: 93%
“…Overall, our study did not show a statistically significant increased risk of stroke in GPA patients compared with their matched controls. This finding is similar to that in a recent study by Faurschou et al in Denmark (51).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast the risk of cerebrovascular disease was not increased after a median follow-up of 7.2 years in 180 Danish GPA patients diagnosed between 1993-2011 [38]. However, the Incidence Rate Ratio (IRR) for deep vein thrombosis (DVT) and pulmonary embolism (PE) was substantially increased within the first two years of diagnosis with an IRR of 25.7 (95% CI 6.9-96) for PE and 20.3 (95% CI 5.1-81) for DVT in the same cohort.…”
Section: Cardiovascularcontrasting
confidence: 50%
“…However, the Incidence Rate Ratio (IRR) for deep vein thrombosis (DVT) and pulmonary embolism (PE) was substantially increased within the first two years of diagnosis with an IRR of 25.7 (95% CI 6.9-96) for PE and 20.3 (95% CI 5.1-81) for DVT in the same cohort. Seventy percent of thrombo-embolic events occurred during episodes of active vasculitis [38].…”
Section: Cardiovascularmentioning
confidence: 99%
“…A recent cohort study comparing 180 GPA patients to matched controls demonstrated a dramatic increase in the risk of pulmonary embolism during the first 2 years of follow-up (incidence rate ratio (IRR) 25.7 (95 % CI 6.9-96)) [57]. This high rate of VTE was also demonstrated in the Wegener's Granulomatosis Etanercept Trial (WGET), in which 29/180 (16 %) of GPA patients experienced VTE a median of 2.1 months after enrollment.…”
Section: Vasculitismentioning
confidence: 98%